The impact of environmental transformational leadership on post-acquisition performance in serbia - Igor Milojević; Andrijana urević; Julija Vidosavljević (Economic Themes, 2024)
External economic and social pressures force manufacturing companies to be ecologically oriented, putting emphasis on issues of environmental protection in the foreground of business policies and strategies. This study explores the role of ecological transformation leadership in acquired production companies in Serbia and examines its impact the on postacquisition performance of companies, assuming that environmental innovation represents mediators of that influence. The survey was conducted based on responses of 91 respondents, i.e. employees from five companies that were part of the acquisition process in Serbia. Collected data was processed in the SPSS program, using statistical analyses such as descriptive statistical analysis, correlational statistical analysis, and regression statistical analysis. Empirical results show that environmental transformational leadership (ETL) has a positive impact on both the environmental (EP) and financial (FP) post-acquisition performance of acquired companies. The results also show that environmental innovation (including environmental innovation strategies (EIS) and ecological innovative activities (EIA)) represent mediators in the relationship between ecological transformational leadership and environmental post-acquisition performance. However, ecological innovations are not a mediator in the relationship between ecological transformation leadership and financial and non-financial post-acquisition performance. Considering the lack of studies investigating the environmental orientation of acquired companies, this study contributes to understanding how companies apply ecological transformation after acquisition leadership and what is its impact on post-acquisition performance.
Keywords: Q56; 330; ecological transformational leadership; innovations; acquisitions; performance